PENGARUH CANDLE THERAPY TERHADAP TINGKAT AFTERPAIN IBU POSTPARTUM - Setyarini, Didien Ika (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2018)
Afterpain is a pain tipically lasts for 2-3 days after birth, this condition is caused by uterine contractions. The use of pharmacological methods can indirectly affect the quality of breast milk and the baby who consumes them. Then, it would be required an alternative method to reduce afterpain. The goal of the research is to determine the influence of Candle Therapy to the level of afterpain. The research is included into pre experiment with taking 10 respondents by purposive sampling. The research design is one group pre-post-test design. Research instruments are colored candles and NRS (Numerical Rating Scale). Results of the study before the Candle Therapy are 10% controlled severe pain, 33% mild pain, and 57% medium pain, whereas after the Candle Therapy are 3% medium pain, 30% no pain, and 67% mild pain. The results were analyzed using Paired T-Test, with df=18 and Î±=0,05 indicates the value of tcount=8,054 and ttable=2,101; so that tcount > ttable. The test result by using SPSS 16 indicates the value of p=0,000, so that p< Î±. Then Ho is rejected. Thus, it can be concluded that there is influence of Candle Therapy to the level of afterpain Keywords: Candle Therapy, afterpain, postpartum women